- Consensus theorem
-
Variable inputs Function values X Y Z xy + x'z + yz xy + x'z 0 0 0 0 0 0 0 1 1 1 0 1 0 0 0 0 1 1 1 1 1 0 0 0 0 1 0 1 0 0 1 1 0 1 1 1 1 1 1 1 In Boolean algebra, the consensus theorem is a simplification of the following terms:
- xy + x'z + yz = xy + x'z
Proof for this theorem is:
LHS = xy + x'z + (x + x' )yz = xy + x'z + xyz + x'yz = xy + xyz + x'z + x'yz = xy(1 + z) + x'z(1 + y) = xy + x'z = RHS
The dual of this equation is:
- (x + y)(x' + z)(y + z) = (x + y)(x' + z)
The consensus term, refers to the redundant term, (y + z). It can be derived from (x+y) and (x' +z) through the resolution inference rule. This shows that the LHS is derivable from the RHS (if A → B then A → AB; replacing A with RHS and B with (y + z) ). The RHS can be derived from the LHS simply through the conjunction elimination inference rule. Since RHS → LHS and LHS → RHS (in propositional calculus), then LHS = RHS (in Boolean algebra).
In digital logic, including the consensus term can eliminate race hazards.
References
- Roth, Charles H. Jr. and Kinney, Larry L. (2004, 2010). "Fundamentals of Logic Design", 6th Ed., p. 66ff.
Categories:
Wikimedia Foundation. 2010.